Fracture mechanics investigation for a 3-D crack in a MRT rail - Lim, Yu Heng (2018)
Fatigue crack growth has always been a concern for railways as it might lead to derailment which causes catastrophic consequences. When the crack is subjected to cyclic rolling contact due to regular movement of the trains, the rate of crack growth greatly increases. Although there were several studies previously done on fatigue crack growth, little research had been done to understand the crack growth due to cyclic loading. Numerical simulations were done to better understand the behaviour of crack growth under different parameters instead of conducting a full-scale experiment with actual scenarios due to the high cost involved. Simulations were done using a finite element software, ABAQUS. A total of 52 two dimensional configurations and 22 three dimensional configurations were simulated with varying conditions to allow observations of trends and behaviours.